1986
DOI: 10.1177/1077727x8601400304
|View full text |Cite
|
Sign up to set email alerts
|

Imported Versus Domestic Blouses: Women's Preferences and Purchase Motives

Abstract: The purpose of this research was to determine women's preferences for either imported or domestic blouses. A questionnaire was distributed to two groups: 114 students at The University of Alabama and 104 women in Tuscaloosa women's clubs. Information was obtained to: determine proportionate numbers of women's imported and domestic blouses purchased by the consumers, iden tify reasons for the consumers' purchases of either imported or domestic blouses, and examine relationships between socioeconomic factors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…On the other hand, a favorable or unfavorable COM reflects consumers' overall perceptions of products made in the country or their stereotypes associated with the country (Nebenzahl et al, 1997). Although some studies found insignificant effects of COM on consumers' perceptions of products (McLean et al, 1986;Sternquist and Davis, 1986), it has been generally agreed that most products originating in foreign countries are subject to COM effects (Brodowsky, 1998;Dickerson, 1982;Han and Terpstra, 1988;Johannson and Nebenzahl, 1986;Shim et al, 1989;Siu and Chan, 1997;Thorelli et al, 1988;Wang and Lamb, 1983). In addition, the COM has been known to affect consumers' evaluations of product-specific attributes as well as overall product quality (Han, 1989;Li and Dant, 1997;Han and Terpstra, 1988;Thakor and Katsanis, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a favorable or unfavorable COM reflects consumers' overall perceptions of products made in the country or their stereotypes associated with the country (Nebenzahl et al, 1997). Although some studies found insignificant effects of COM on consumers' perceptions of products (McLean et al, 1986;Sternquist and Davis, 1986), it has been generally agreed that most products originating in foreign countries are subject to COM effects (Brodowsky, 1998;Dickerson, 1982;Han and Terpstra, 1988;Johannson and Nebenzahl, 1986;Shim et al, 1989;Siu and Chan, 1997;Thorelli et al, 1988;Wang and Lamb, 1983). In addition, the COM has been known to affect consumers' evaluations of product-specific attributes as well as overall product quality (Han, 1989;Li and Dant, 1997;Han and Terpstra, 1988;Thakor and Katsanis, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluative criteria were de-fined as "the particular dimensions or attributes that are used in judging the choice alternatives" (Engel, et al, 1995, p. 208). Researchers have found the most important evaluative criteria related to clothing to be price, style or design, suitability or appropriateness for a specific situation, fiber content, cut or fit, how pleasing it was to others, coordination with other clothing, comfort, and color or pattern (Davis, 1987;Eckman, et al, 1990;Jenkins, 1973;Martin 1971-72;McLean, et al, 1986;Workman, 1990). However, the terms used and the way in which criteria have been classified have varied among the studies.…”
mentioning
confidence: 99%
“…Because individuals appear to hold specific attitudes, both positive and negative, toward imported and domestically produced clothing, it could be predicted that labels disclosing country-of-origin information should influence an individual's evaluation of a garment. However, research by Sternquist and Davis (1986) and McLean, Roper, and Smothers (1986), indicated that country-of-origin information did not influence the ratings of either the quality or the price of an apparel item. These findings need to be interpreted with caution, as Sternquist and Davis (1986) actually controlled for the quality of the apparel item by having all subjects look at the same apparel item, but labeling it with different country-of-origin information.…”
mentioning
confidence: 93%
“…Although both brand name and size may be associated with perceptions of quality, research by McLean, Roper, and Smothers (1986) indicated that brand name may not serve as a purchase motivation. These researchers asked subjects to rank order nine motives for purchasing a blouse.…”
mentioning
confidence: 99%